2016
DOI: 10.5114/fmpcr/63461
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged consumption of energy drinks does not affect the processes of memory, and increases the activity of transaminases, and cholesterol concentration – animal model study results

Abstract: A -Study Design, B -Data Collection, C -Statistical analysis, D -Data interpretation, E -Manuscript Preparation, F -Literature Search, G -Funds CollectionBackground. the consumption of energy drinks (ed) is popular among young people. there are concerns that it could be harmful for their health. Objectives. the aim of the study was to analyze the influence of ed consumption on animals for 30 subsequent days on memory, weight gain and biochemical parameters (alanine transaminase-aLt, asparagine transaminase-ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It was found that EDs induce several adverse effects but the most common is cardiovascular, neurological, and liver impairment, with no positive effect on the memory process (Ali et al, 2015;Nieradko-Iwanicka & Pośnik, 2016). Theses side effects were mainly related to the high content of caffeine in addition to the effect of the other ingredients included in these drinks (Gheith, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that EDs induce several adverse effects but the most common is cardiovascular, neurological, and liver impairment, with no positive effect on the memory process (Ali et al, 2015;Nieradko-Iwanicka & Pośnik, 2016). Theses side effects were mainly related to the high content of caffeine in addition to the effect of the other ingredients included in these drinks (Gheith, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, CafSuc and control treatment groups showed intact place recognition and novel object recognition memory. This indicates that the addition of caffeine to sucrose solution may protect against sucrose-evoked cognitive deficits in hippocampal-mediated memory (Nieradko-Iwanicka et al, 2016) and caffeine may improve hippocampal function (Ardais et al, 2014;Sahu et al, 2013). Furthermore, CafSuc treatment improved long-term object memory performance relative to Suc treatment, demonstrating that the addition of caffeine to sucrose may enhance aspects of memory consolidation.…”
Section: Discussionmentioning
confidence: 90%
“…Despite the generally cognitive enhancing properties of caffeine, sugar-sweetened energy drinks have been linked to both positive (Wesnes et al, 2017) and negative (Van Batenburg-Eddes et al, 2014) cognitive outcomes. A recent study suggested that the addition of caffeine to sucrose solution may protect against sucrose-induced deficits in hippocampal-mediated memory, as mice with 10% sucrose + 0.03% caffeine access for 30 days showed intact place memory in the Y-Maze (Nieradko-Iwanicka et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At higher doses, they observed renal vascular congestion, the bleeding of interstitial tissue, focal atrophy, and the degeneration of the lining epithelium of the proximal and distal convoluted tubules. Nieradko Iwanicka and colleagues [ 122 ] studied the effects of the ad libitum consumption of energy drinks in mice on memory, body weight and laboratory parameters. After 30 days of the experiment, the researchers observed weight gain in male mice, an increase in serum transaminases and cholesterol concentration, but no memory-related changes.…”
Section: Discussionmentioning
confidence: 99%